Clonidine Use for the Treatment of Nightmares in Posttraumatic Stress Disorder - Jill S. Bange; Kelly E. Melvin (Case Reports in Psychiatry)
Introduction. While clonidine is used clinically for the treatment of nightmares in posttraumatic stress disorder (PTSD), few case reports demonstrating this indication exist, and there have been few studies investigating clonidine’s mechanism of action for controlling nightmare symptoms. Case Report. In order to further characterize clonidine’s role in treating nightmare symptoms in PTSD, we offer this case report describing one United States veteran who presented to an inpatient psychiatric unit after a suicide attempt. At that time, she described a remote history of PTSD symptoms, including nightmares, flashbacks, hyperarousal, and avoidance behaviors which had been well controlled on sertraline and clonidine. Upon her admission, her home sertraline and alprazolam were continued but her home clonidine was not continued. On day two of her hospital stay, she stated that her nightmares had returned. Her home clonidine was restarted on day two. On day three and thereafter, the patient no longer complained of nightmares. Conclusion. Our patient’s nightmare symptoms had been controlled for years after beginning clonidine as an outpatient, but off clonidine, she had a return of her nightmare symptoms. Her nightmares again resolved once clonidine was resumed. Given this pattern in the patient’s response to clonidine, this case may serve as additional evidence in the literature that clonidine has a role in treating nightmares in PTSD. Current proposed mechanisms of action for clonidine’s ability to control nightmare symptoms in PTSD include that clonidine may alter the proportions of REM and non-REM sleep in a dose-dependent manner or that clonidine may play a role in memory consolidation. Further formal medication trials are the ideal future direction for establishing this role for clonidine.